A preparation method of nano silicon carbon negative electrode precursor and nano silicon carbon negative electrode material
By mixing the organic carbon source and silicon source, and the use of aluminum heat -burning to cause oxidation and reduction reaction, the nano -silicon carbon negative anode front -drive body is prepared to solve the problem of low capacity of lithium -ion batteries. , Simplified process processes and excellent electrochemical properties.
Patent Information
- Application Number
- CN202410677987.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-29
Smart Images

Figure CN118439615B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a method for preparing a nano silicon-carbon negative electrode precursor and a nano silicon-carbon negative electrode material. Background Art
[0002] At present, the negative electrode material of lithium-ion batteries is mainly graphite, but its low theoretical specific capacity of 372mAh / g has hindered the further improvement of the specific capacity of lithium-ion batteries. Silicon-based negative electrodes have extremely high theoretical specific capacity (pure silicon negative electrodes are 4200mAh / g, 11 times that of graphite materials) and low lithium insertion potential (less than 0.4V), and are the next generation of high energy density lithium-ion battery negative electrode materials with great potential and development prospects.
[0003] However, the application of silicon-based negative electrode materials still has the following problems: ① The volume expansion rate of silicon when embedded with lithium is high (about 300%), which easily causes the material to break and pulverize, resulting in poor cycle stability of silicon negative electrode materials; ② The conductivity of silicon materials is poor.
[0004] The solutions to the above problems mainly include: ① reducing the particle size of silicon materials and preparing nano-silicon with a particle size less than 100nm; ② using carbon materials with good conductivity and low volume expansion rate as coating layers to prepare core-shell structured nano-silicon-carbon negative electrode materials, thereby improving the cycle stability and conductivity of silicon-carbon negative electrode materials.
[0005] At present, the preparation process of nano silicon carbon negative electrode materials mainly adopts chemical vapor deposition (CVD). The overall preparation time of the material is more than 10 hours, with a long cycle and high energy consumption; and the CVD method requires large equipment investment, complex process and high cost.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a nano silicon-carbon negative electrode precursor and a nano silicon-carbon negative electrode material to solve or improve the above technical problems.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides a method for preparing a nano silicon carbon negative electrode precursor, which comprises:
[0010] mixing an organic carbon source and a silicon source to obtain a mixed powder;
[0011] The mixed powder is ignited by thermite to induce a redox reaction of the mixed powder to obtain a negative electrode precursor.
[0012] In an optional embodiment, the mass fraction of the thermite in the mixed powder is 1%-5%;
[0013] And / or, the thermite comprises aluminum powder and ferric oxide powder in a mass ratio of (0.1-0.5):1.
[0014] In an optional embodiment, the ignition method includes: inserting a magnesium bar into the thermite, igniting the magnesium bar to ignite the thermite, and initiating a redox reaction of the mixed powder;
[0015] Preferably, the redox reaction is carried out in a closed or semi-closed container;
[0016] Preferably, the container is provided with a groove for placing the thermite and a plane for spreading the mixed powder, the plane is connected to the side wall of the groove in an annular manner, and the thermite and the mixed powder are in contact with each other at the end of the groove;
[0017] Preferably, the magnesium strip is ignited using a pulse igniter.
[0018] In an optional embodiment, the mass ratio of the organic carbon source to the silicon source in the mixed powder is (0.5-2):1;
[0019] And / or, the organic carbon source is a polymer, and the monomer of the polymer includes at least one of ethylene, propylene, vinyl acetate, vinyl alcohol and ethylene glycol;
[0020] And / or, the particle size of the organic carbon source is 1 μm to 70 μm, preferably 1 μm to 2 μm;
[0021] And / or, the silicon source includes at least one of micron silicon, nano silicon and silicon carbide;
[0022] And / or, the particle size of the silicon source is 200 nm to 3 μm, preferably 600 nm to 800 nm.
[0023] In an optional embodiment, the polymer comprises one or more of a homopolymer or a copolymer composed of the monomers;
[0024] Preferably, the copolymer comprises at least one of ethylene-propylene copolymer and ethylene-vinyl acetate copolymer;
[0025] Preferably, the molecular formula of the ethylene-propylene copolymer is (CH2CH2-CH3CHCH2) m or (CH2CH2) a (CH2CHCH2) b , where m ranges from 200 to 1000, and a:b ranges from (4 to 10):1;
[0026] Preferably, the molecular formula of the ethylene-vinyl acetate copolymer is (CH2CH2-CH2CHCOOCH3) m or (CH2CH2) a (CH2CHCOOCH3) b , where m ranges from 300 to 800, and a:b ranges from (2 to 6):1.
[0027] In an optional embodiment, when mixing the organic carbon source and the silicon source, a dispersant is further added;
[0028] Preferably, the total mass fraction of the organic carbon source and the silicon source in the mixed powder is 97% to 99.5%, and the mass fraction of the dispersant is 0.5% to 3%;
[0029] Preferably, the dispersant includes at least one of PE wax powder, polyacrylate, sulfonate and hydroxyethyl cellulose.
[0030] In an optional embodiment, the mixing comprises at least one of stirring, ball milling and grinding;
[0031] Preferably, the ball milling speed is 300-800 rpm, and the ball milling time is 1-10 h.
[0032] In a second aspect, the present invention provides a nano silicon-carbon negative electrode material, which is prepared by post-processing a nano silicon-carbon negative electrode precursor prepared by the method for preparing a nano silicon-carbon negative electrode precursor as described in any of the aforementioned embodiments.
[0033] In an optional embodiment, the post-treatment includes pickling, washing and drying the nano silicon carbon negative electrode precursor;
[0034] Preferably, the pickling comprises washing with a pickling solution having a concentration of 0.5 to 1.5 mol / L;
[0035] Preferably, the pickling solution comprises at least one of hydrochloric acid, sulfuric acid or nitric acid;
[0036] And / or, the washing comprises washing with an ethanol-water solution, wherein the mass ratio of ethanol to water in the ethanol-water solution is (0.5-2):1;
[0037] And / or, the drying temperature is 50-80° C. and the drying time is 3-6 hours.
[0038] In an optional embodiment, the particle size of the nano silicon carbon negative electrode material is 20 nm to 1 μm, preferably 100 nm to 700 nm, and more preferably 200 nm to 500 nm.
[0039] The present invention has the following beneficial effects:
[0040] The preparation method of the nano silicon-carbon negative electrode precursor provided by the present invention is to mix an organic carbon source and a silicon source to achieve uniform dispersion of the mixed powder, and then use the mixed powder as a reactant, and use the combustion of thermite to provide heat. When the combustion temperature reaches the reaction threshold condition, the organic carbon source and the silicon source undergo a violent redox reaction to generate a carbon shell, and at the same time, the energy released by the combustion causes the unreacted silicon source particles to crack and break at high temperature to form nano silicon, thereby obtaining a nano silicon-carbon negative electrode precursor, simplifying the process. In addition, when the organic carbon source and the silicon source undergo a self-propagating reaction, the generated silicon-carbon material is quickly sprayed into the space, so that the aluminum oxide particles generated by the combustion of thermite rub and collide with the silicon-carbon material. In this process, the aluminum oxide has an interface modification and shaping effect on the outer surface of the coated carbon layer, which improves the unevenness of the outer surface of the carbon layer. After the pole piece is made, the contact area between the outer surface of the carbon layer and other materials is increased, thereby improving the electrical performance of the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0042] Figure 1 This is a scanning electron microscope image of the nano silicon carbon negative electrode material prepared in Example 3;
[0043] Figure 2 This is a charge and discharge cycle performance curve of the nano silicon carbon negative electrode material prepared in Example 3. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0045] The following is a detailed description of the preparation method of the nano silicon carbon negative electrode precursor and the nano silicon carbon negative electrode material provided in the present application.
[0046] The invention provides a method for preparing a nano silicon-carbon negative electrode precursor, which comprises the following steps: mixing an organic carbon source and a silicon source to obtain a mixed powder; igniting the mixed powder with a thermite to induce a redox reaction of the mixed powder to obtain a negative electrode precursor.
[0047] The method achieves uniform dispersion of the mixed powder by mixing an organic carbon source and a silicon source, and then uses the mixed powder as a reactant and utilizes the combustion of thermite to provide heat. When the combustion temperature reaches the reaction threshold condition, the organic carbon source and the silicon source undergo a violent redox reaction to generate a carbon shell. At the same time, the energy released by the combustion causes the unreacted silicon source particles to crack and break at high temperature to form nano-silicon, thereby obtaining a nano-silicon-carbon negative electrode precursor, which simplifies the process. In addition, when the organic carbon source and the silicon source undergo a self-propagating reaction, the generated silicon-carbon material is quickly sprayed into the space, causing the aluminum oxide particles generated by the combustion of thermite to rub and collide with the silicon-carbon material. In this process, the aluminum oxide has an interface modification and shaping effect on the outer surface of the coated carbon layer, thereby improving the unevenness of the outer surface of the carbon layer. After the pole piece is made, the contact area between the outer surface of the carbon layer and other materials is increased, and the outer surface carbon layer and other materials can form a larger number of conductive paths, thereby improving the electrical performance of the pole piece.
[0048] Next, the present invention will elaborate on the above steps in detail.
[0049] S1. Mixing an organic carbon source and a silicon source to obtain a mixed powder.
[0050] In the present invention, the mass ratio of the organic carbon source to the silicon source is (0.5-2):1. In some embodiments, the mass ratio of the organic carbon source to the silicon source can be, for example, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1, or any other value within the range of (0.5-2):1 or any range value between the two. In some preferred embodiments, the mass ratio of the organic carbon source to the silicon source can be (0.7-1.5):1. In some more preferred embodiments, the mass ratio of the organic carbon source to the silicon source can be (1-1.5):1. Controlling the mass ratio of the organic carbon source to the silicon source within the above range is more conducive to the coating of silicon by carbon during the redox reaction.
[0051] The organic carbon source is a polymer, and the monomer of the polymer includes at least one monomer selected from ethylene, propylene, vinyl acetate, vinyl alcohol and ethylene glycol.
[0052] Among them, ethylene monomer can be expressed as Propylene monomer can be expressed as Vinyl acetate monomer can be expressed as Vinyl alcohol monomer can be expressed as Ethylene glycol monomer can be expressed as
[0053] The polymer can be a homopolymer composed only of the above-mentioned monomers, a copolymer composed only of the above-mentioned monomers, or a mixture of a homopolymer and a copolymer. The above-mentioned monomers and the above-mentioned copolymers provided by the present invention are conventional bulk raw materials in the market, are cheap and easy to obtain, and can provide more carbon content per unit mass in the preparation process of nano silicon carbon negative electrode precursor.
[0054] The copolymer includes at least one of an ethylene-propylene copolymer and an ethylene-vinyl acetate copolymer.
[0055] The present invention provides a typical but non-limiting example, the molecular formula of ethylene-propylene copolymer is (CH2CH2-CH3CHCH2) m or (CH2CH2) a (CH2CHCH2) b , wherein m ranges from 200 to 1000, for example, it can be any one of 200, 300, 400, 500, 600, 700, 800, 900 and 1000 or a range value between any two; a:b ranges from (4 to 10):1, for example, it can be any one of 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range value between any two. The organic carbon source provided in this example can be used to obtain a nano silicon-carbon negative electrode precursor with relatively higher overall structural strength, first efficiency and capacity retention rate.
[0056] The present invention provides a typical but non-limiting example, the molecular formula of ethylene-vinyl acetate copolymer is (CH2CH2-CH2CHCOOCH3) m or (CH2CH2) a (CH2CHCOOCH3) b , wherein m ranges from 300 to 800, for example, it can be any one of 300, 400, 500, 600, 700, 800 or a range value between any two of them; the range of a:b is (2 to 6):1, for example, it can be any one of 2:1, 3:1, 4:1, 5:1, 6:1 or a range value between any two of them.
[0057] In the product made using the organic carbon source provided in this example, the carbon layer itself has stronger deformation ability and toughness. Even after the nano-silicon undergoes multiple large-scale volume expansion and contraction, the carbon layer is not easy to crack or disintegrate. Moreover, the carbon layer can always adaptively fit tightly to the surface of the silicon particles, and the resulting electrode product has high cycle stability.
[0058] The present invention does not limit the source of the organic carbon source, and common commercially available industrial-grade products can be used. The particle size of the organic carbon source can be 1 μm to 70 μm, such as 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm or 70 μm, or any range between two of them. In some preferred embodiments, the particle size of the organic carbon source is 1 μm to 5 μm. In some more preferred embodiments, the particle size of the organic carbon source is 1 μm to 2 μm. The use of an organic carbon source in the above particle size range is conducive to obtaining a better uniform dispersion effect.
[0059] The present invention does not limit the source of the silicon source, and any common commercially available industrial-grade product may be used. For example, the silicon source may exemplarily include at least one of micron silicon, nano silicon and silicon carbide.
[0060] In some embodiments, the particle size of the silicon source may be 200 nm to 3 μm, such as any one of 200 nm, 500 nm, 800 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, or a range between any two thereof. In some preferred embodiments, the particle size of the silicon source may be 500 nm to 2 μm. In some more preferred embodiments, the particle size of the silicon source may be 600 nm to 800 nm. Using a silicon source in the above particle size range is conducive to obtaining a better uniform dispersion effect.
[0061] Furthermore, when mixing the organic carbon source and the silicon source, in order to improve the dispersion uniformity of the organic carbon source and the silicon source, a dispersant can be added for mixing. When the dispersant is added, the total mass fraction of the organic carbon source and the silicon source in the mixed powder is 97% to 99.5%, and the mass fraction of the dispersant is 0.5% to 3%.
[0062] In some embodiments, the total mass of the organic carbon source and the silicon source can be 97% to 99.5% of the mixed powder, such as 97%, 97.5%, 97.8%, 98%, 98.5%, 99% or 99.5%, etc., or any other value within the range of 97% to 99.5% or any range value between the two. In some preferred embodiments, the total mass of the organic carbon source and the silicon source can be 97.5% to 99.5% of the mixed powder. In some more preferred embodiments, the total mass of the organic carbon source and the silicon source can be 97.8% to 99.2% of the mixed powder. Controlling the total mass of the organic carbon source and the silicon source within the above range is more conducive to the coating of silicon by carbon.
[0063] In some embodiments, the mass of the dispersant can be 0.5% to 3% of the mixed powder, such as 0.5%, 1%, 1.5%, 2%, 2.5% or 3%, etc., or any other value within the range of 0.5% to 3% or any range value between the two. In some preferred embodiments, the mass of the dispersant can be 0.8% to 2.2% of the mixed powder. In some more preferred embodiments, the mass of the dispersant can be 1% to 1.5% of the mixed powder. Using the dispersant in the above dosage range can ensure that the organic carbon source and the silicon source are evenly dispersed.
[0064] The present invention does not limit the source of the dispersant, and any common commercially available industrial-grade product can be used. For example, the dispersant may exemplarily include at least one of PE wax powder, polyacrylate, sulfonate, and hydroxyethyl cellulose. The dispersant can not only improve the dispersion effect, but also increase the surface activity of the organic carbon source and silicon source particles, achieve microscopic control of the silicon / carbon interface, and reduce the volume expansion of the silicon material.
[0065] The present invention has no special limitation on the mixing operation, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted. Mixing can illustratively include at least one of stirring, ball milling and grinding; preferably, the ball milling speed is 300-800 rpm, and the ball milling time is 1-10 hours. Preferably, the ball milling speed is 400-600 rpm, and the ball milling time is 2-5 hours. The present invention has no special limitation on the ball-to-material ratio of ball milling, and the ball-to-material ratio well known to those skilled in the art can be adopted. In the present invention, the ball milling speed and time within the above range can mix the organic carbon source particles and the silicon source particles evenly, so as to carry out subsequent operations.
[0066] S2. Ignite the mixed powder with thermite to induce a redox reaction of the mixed powder to obtain a negative electrode precursor.
[0067] In the present invention, the thermite is ignited to initiate a redox reaction in the mixed powder, so that a violent reaction of an organic carbon source and a silicon source in the mixed powder can be achieved, wherein the mass fraction of the thermite in the mixed powder is 1%-5%, for example, it can be 1%, 2%, 3%, 4% or 5%, or any other value within the range of 1% to 5%, or any range value between the two; the thermite comprises aluminum powder and ferric oxide powder in a mass ratio of (0.1 to 0.5):1, and the mass ratio of the aluminum powder to the ferric oxide powder can be, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1 or 0.5:1, or any other value within the range of (0.1 to 0.5):1, or any range value between the two.
[0068] The present invention does not limit the source of thermite, and any common commercially available industrial grade product can be used. Figure 1It can be seen that the thermite has an interface modification and shaping effect on the outer surface of the coated carbon layer, and the particle morphology is consistent, which is beneficial to improving the performance of the electrode.
[0069] The redox reaction in the present invention is carried out in a closed or semi-closed container; the setting of the closed or semi-closed container can prevent the redox reaction of the organic carbon source particles and the silicon source particles in an open environment from being too intense, which will produce a large amount of SiH4 gas and make some products difficult to effectively recover and treat.
[0070] There are many options for closed or semi-closed containers, including but not limited to reaction crucibles. The closed or semi-closed container in the present invention takes a reaction crucible as an example. The reaction crucible in the present invention is different from a conventional crucible. It is provided with a groove for placing thermite and a plane for spreading the mixed powder. The plane is connected to the side wall of the groove in a ring. Thermite and the mixed powder are in contact with each other at the end of the groove. When the temperature generated by the heat released by the combustion of thermite reaches the reaction threshold of the mixed powder, the mixed powder can be triggered to undergo an oxidation-reduction reaction, which is a self-propagating reaction.
[0071] The ignition method includes: inserting a magnesium bar into thermite, igniting the magnesium bar to ignite thermite, and initiating a redox reaction in the mixed powder; the way to ignite the magnesium bar includes but is not limited to igniting the magnesium bar using a pulse igniter.
[0072] The present invention has no special restriction on the time of the redox reaction. When the flame is extinguished, the reaction ends and a negative electrode precursor is obtained.
[0073] As mentioned above, the preparation method of the nano silicon-carbon negative electrode precursor provided by the present invention is to mix the organic carbon source and the silicon source to achieve uniform dispersion of the mixed powder, and then use the mixed powder as a reactant, and use the combustion of thermite to provide heat. When the combustion temperature reaches the reaction threshold condition, the organic carbon source and the silicon source undergo a violent redox reaction to generate a carbon shell. At the same time, the energy released by the combustion causes the unreacted silicon source particles to crack and break at high temperature to form nano silicon, thereby obtaining a nano silicon-carbon negative electrode precursor, which simplifies the process. In addition, when the organic carbon source and the silicon source undergo a self-propagating reaction, the generated silicon-carbon material is quickly sprayed into the space, so that the aluminum oxide particles generated by the combustion of thermite rub and collide with the silicon-carbon material. In this process, the aluminum oxide has an interface modification and shaping effect on the outer surface of the coated carbon layer, which improves the unevenness of the outer surface of the carbon layer. After the pole piece is made, the contact area between the outer surface of the carbon layer and other materials is increased, thereby improving the electrical performance of the pole piece.
[0074] In addition, the present invention also provides a nano silicon-carbon negative electrode material, and the preparation method thereof comprises acid washing, washing and drying the above-mentioned negative electrode precursor to obtain the nano silicon-carbon negative electrode material.
[0075] Specifically, the following steps are included:
[0076] (1) Pickling.
[0077] In the present invention, pickling includes washing with a pickling solution with a concentration of 0.5 to 1.5 mol / L; preferably, the pickling solution includes at least one of hydrochloric acid, sulfuric acid or nitric acid; the concentration of the pickling solution can be, for example, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L or 1.5 mol / L, or any other value within the range of 0.5 to 1.5 mol / L or any range value between the two.
[0078] (2) Washing.
[0079] In the present invention, washing includes washing with an ethanol-water solution, wherein the mass ratio of ethanol to water in the ethanol-water solution is (0.5-2):1; for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1, or any other value within the range of (0.5-2):1 or any range value between the two.
[0080] (3) Drying.
[0081] In the present invention, the drying can be performed in an oven, illustratively but not limitedly.
[0082] In some embodiments, the drying temperature is 50-80° C., for example, 50° C., 60° C., 70° C. or 80° C., or any other value within the range of 50-80° C. or any range between the two. The drying time is 3-6 hours, for example, 3 hours, 4 hours, 5 hours or 6 hours, or any other value within the range of 3-6 hours or any range between the two.
[0083] In some embodiments, the particle size of the nano silicon carbon negative electrode material can be 20nm to 1μm, such as 20nm, 50nm, 100nm, 200nm, 500nm, 800nm or 1μm, etc., or any other value within the range of 20nm to 1μm. In some preferred embodiments, the particle size of the nano silicon carbon negative electrode material is 100nm to 700nm. In some more preferred embodiments, the particle size of the nano silicon carbon negative electrode material is 200nm to 500nm.
[0084] The nano silicon-carbon negative electrode material can be further used to prepare lithium-ion batteries, so that the lithium-ion batteries have good cycle specific capacity and high specific capacity.
[0085] Illustratively, the nano silicon-carbon negative electrode material provided by the present invention is used as a negative electrode material for a lithium-ion battery, and a charge-discharge cycle performance test is carried out at a charge-discharge rate of 0.2C. After 100 cycles, the capacity can be maintained at 960 mAh / g or above.
[0086] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0087] Example 1
[0088] This embodiment provides a nano silicon carbon negative electrode material, and the preparation method thereof includes:
[0089] S1. 24.5 g of polyethylene particles with a particle size of 1.5 μm, 24.5 g of nano-silicon with a particle size of 800 nm, and 1 g of PE wax powder were mixed and ball-milled for 2 h at a rotation speed of 700 rpm. After the ball milling was completed, a mixed powder was obtained.
[0090] S2. Weigh 10g of the mixed powder obtained above and 0.4g of thermite (the mass ratio of aluminum powder to ferric oxide powder is 0.3:1) and place them in a crucible in a closed container. Insert a magnesium bar into the thermite and ignite the magnesium bar using a pulse igniter. When the burning magnesium bar ignites the thermite, the mixed powder undergoes a redox reaction. After the combustion is completed, the negative electrode precursor can be collected.
[0091] S3. First, the collected negative electrode precursor is placed in a 0.5 mol / L hydrochloric acid aqueous solution for pickling and filtering, and then placed in an ethanol / water solution with a mass ratio of 1:1 for washing and filtering. Finally, the filtered product is placed in a forced air drying oven at 60°C for 3 hours to obtain a nano-silicon-carbon negative electrode material with a particle size of 300 to 600 nm.
[0092] The nano silicon-carbon negative electrode material prepared in this example is used as a negative electrode material for lithium-ion batteries, and it is found that it has excellent cycle specific capacity and high first coulombic efficiency.
[0093] Example 2
[0094] This embodiment provides a nano silicon carbon negative electrode material, and the preparation method thereof includes:
[0095] S1. 16.5 g of polypropylene particles with a particle size of 2 μm, 32.5 g of micronized silicon with a particle size of 1 μm, and 1 g of carboxyethyl cellulose were mixed and ball-milled for 3 h at a rotation speed of 600 rpm. After the ball-milling was completed, a mixed powder was obtained.
[0096] S2. Weigh 10g of the mixed powder obtained above and 0.5g of thermite (the mass ratio of aluminum powder to ferric oxide powder is 0.3:1) and place them in a crucible in a closed container. Insert a magnesium bar into the thermite and ignite the magnesium bar using a pulse igniter. When the burning magnesium bar ignites the thermite, the mixed powder undergoes a redox reaction. After the combustion is completed, the negative electrode precursor can be collected.
[0097] S3. First, the collected negative electrode precursor is placed in a 0.5 mol / L hydrochloric acid aqueous solution for pickling and filtering, and then placed in an ethanol / water solution with a mass ratio of 1:1 for washing and filtering. Finally, the filtered product is placed in a forced air drying oven at 80°C for 3 hours to obtain a nano-silicon-carbon negative electrode material with a particle size of 400 to 600 nm.
[0098] The nano silicon-carbon negative electrode material prepared in this example is used as a negative electrode material for lithium-ion batteries, and it is found that it has excellent cycle specific capacity and high first coulombic efficiency.
[0099] Example 3
[0100] This embodiment provides a nano silicon carbon negative electrode material, and the preparation method thereof includes:
[0101] S1. 24.4 g of polyvinyl alcohol particles with a particle size of 1 μm, 24.4 g of nano-silicon with a particle size of 800 nm, 0.6 g of sulfonate, and 0.6 g of hydroxyethyl cellulose were mixed and ball-milled for 3 h at a rotation speed of 600 rpm. After the ball-milling was completed, a mixed powder was obtained.
[0102] S2. Weigh 10g of the mixed powder obtained above and 0.2g of thermite (the mass ratio of aluminum powder to ferric oxide powder is 0.3:1) and place them in a crucible in a closed container. Insert a magnesium bar into the thermite and ignite the magnesium bar using a pulse igniter. When the burning magnesium bar ignites the thermite, the mixed powder undergoes a redox reaction. After the combustion is completed, the negative electrode precursor can be collected.
[0103] S3, firstly wash and filter the collected negative electrode precursor in 0.8mol / L hydrochloric acid aqueous solution, then wash and filter in ethanol / water solution with a mass ratio of 1.2:1, and finally dry the filtered product in a 65℃ forced air drying oven for 5h to obtain a nano silicon-carbon negative electrode material with a particle size of 200-400nm. Figure 1 It can be seen that the nano silicon-carbon negative electrode material prepared in this embodiment has good consistency in particle morphology.
[0104] The nano silicon carbon negative electrode material prepared in this example is used as a negative electrode material for lithium ion batteries. Figure 2 It can be seen that it has excellent cycle specific capacity and high first coulombic efficiency.
[0105] Example 4
[0106] This embodiment provides a nano silicon carbon negative electrode material, and the preparation method thereof includes:
[0107] S1. 27 g of polyethylene glycol particles with a particle size of 1 μm, 22 g of silicon carbide with a particle size of 1 μm, and 1.2 g of polyacrylate dispersant were mixed and ball-milled for 3 h at a rotation speed of 600 rpm. After the ball-milling was completed, a mixed powder was obtained.
[0108] S2. Weigh 10g of the mixed powder obtained above and 0.3g of thermite (the mass ratio of aluminum powder to ferric oxide powder is 0.3:1) and place them in a crucible in a closed container. Insert a magnesium bar into the thermite and ignite the magnesium bar using a pulse igniter. When the burning magnesium bar ignites the thermite, the mixed powder undergoes a redox reaction. After the combustion is completed, the negative electrode precursor can be collected.
[0109] S3. First, the collected negative electrode precursor is placed in a 0.7 mol / L hydrochloric acid aqueous solution for pickling and filtering, and then placed in an ethanol / water solution with a mass ratio of 1.2:1 for washing and filtering. Finally, the filtered product is placed in a forced air drying oven at 65°C for 5 hours to obtain a nano-silicon-carbon negative electrode material with a particle size of 200 to 400 nm.
[0110] The nano silicon-carbon negative electrode material prepared in this example is used as a negative electrode material for lithium-ion batteries, and it is found that it has excellent cycle specific capacity and high first coulombic efficiency.
[0111] Example 5
[0112] The difference between this embodiment and embodiment 4 is that in S1, the organic carbon source is copolymer particles of ethylene and propylene (CH2CH2) a (CH2CHCH2) b , where a:b=4:1.
[0113] Example 6
[0114] The difference between this embodiment and embodiment 4 is that in S1, the organic carbon source is copolymer particles of ethylene and propylene (CH2CH2) a (CH2CHCH2) b , where a:b=7:1.
[0115] Example 7
[0116] The difference between this embodiment and embodiment 4 is that in S1, the organic carbon source is copolymer particles of ethylene and propylene (CH2CH2) a (CH2CHCH2) b , where a:b=10:1.
[0117] Example 8
[0118] The difference between this embodiment and embodiment 4 is that in S1, the organic carbon source is copolymer particles of ethylene and vinyl acetate (CH2CH2) a (CH2CHCOOCH3) b , where a:b=2:1.
[0119] Example 9
[0120] The difference between this embodiment and embodiment 4 is that in S1, the organic carbon source is copolymer particles of ethylene and vinyl acetate (CH2CH2) a (CH2CHCOOCH3) b , where a:b=4:1.
[0121] Example 10
[0122] The difference between this embodiment and embodiment 4 is that in S1, the organic carbon source is copolymer particles of ethylene and vinyl acetate (CH2CH2) a (CH2CHCOOCH3) b , where a:b=6:1.
[0123] Embodiment 11
[0124] The difference between this embodiment and embodiment 1 is that the dispersant PE wax powder is omitted in S1. At this time, the mass of the polyethylene particles is 25 g, and the mass of the nano-silicon is 25 g.
[0125] Comparative Example 1
[0126] The difference between this embodiment and embodiment 10 is that in S1, sodium lauryl sulfate is used as the dispersant instead of polyacrylate.
[0127] Comparative Example 2
[0128] The difference between this embodiment and embodiment 10 is that in S1, the ball milling time is 12 hours.
[0129] Comparative Example 3
[0130] The difference between this embodiment and embodiment 10 is that in S3, the drying time is 2 hours.
[0131] Comparative Example 4
[0132] The difference between this comparative example and Example 10 is that in S1, the organic carbon source is copolymer particles of vinyl chloride and vinylidene chloride (CH2CHCl) a (CH2CCl2) b , where a:b=6:1.
[0133] Comparative Example 5
[0134] The difference between this comparative example and Example 10 is that in S1, the organic carbon source is copolymer particles of propylene and isobutylene (CH3CHCH2) a (CH2C(CH3)2) b , where a:b=6:1.
[0135] Comparative Example 6
[0136] The difference between this comparative example and Example 10 is that in S2, the amount of thermite used is 1 g.
[0137] Comparative Example 7
[0138] The difference between this comparative example and Example 10 is that S2 is different and step S3 is omitted. Step S2 in this comparative example includes: weighing 10g of the mixed powder obtained above and placing it in a closed container, the pressure of the closed container is standard atmospheric pressure, and the container is filled with air, and then using a microwave heating device to heat the mixed powder. The power of the microwave heating is 2.2kW. When the temperature reaches 1100°C, an oxidation-reduction reaction is carried out, and the reaction is a self-propagating reaction. After 10 minutes, the product is collected to obtain a carbon-coated nano-silicon negative electrode material with a particle size of 20nm to 600nm.
[0139] Comparative Example 8
[0140] The difference between this comparative example and Example 10 is that S2 is different. In this comparative example, 10g of the mixed powder obtained above and 0.3g of thermite (the mass ratio of aluminum powder to ferric oxide powder is 0.3:1) are weighed and mixed evenly in advance, then placed in a crucible in a closed container, a magnesium bar is inserted into the mixture, and the magnesium bar is ignited using a pulse igniter. When the burning magnesium bar ignites the mixture to undergo an oxidation-reduction reaction, the negative electrode precursor can be collected after the combustion is completed.
[0141] Comparative Example 9
[0142] The difference between this comparative example and Example 10 is that S2 is different. In this comparative example, 10 g of the mixed powder obtained above is weighed, and then placed in a crucible in a closed container. A pulse igniter is used to ignite the mixed powder, and the mixed powder undergoes a redox reaction. After the combustion is completed, the negative electrode precursor can be collected.
[0143] Experimental example
[0144] Taking the nano silicon carbon negative electrode precursors prepared in Examples 1 to 11 and Comparative Examples 1-9 as examples, button batteries were prepared in the following manner, and the first coulombic efficiency and the material specific capacity after 100 cycles were tested under a 0.2C battery charge and discharge rate condition. The results are shown in Table 1.
[0145] Preparation method of button cell: use the nano silicon carbon negative electrode precursor of the above embodiment: acetylene black: polyvinylidene fluoride = 8:1:1 (weight ratio), add appropriate amount of NMP to make battery slurry, then grind and mix the slurry in an agate mortar, apply the mixture on copper foil and dry it in a vacuum drying oven for 12 hours to make a negative electrode sheet, metal lithium sheet as counter electrode and reference electrode, electrolyte is 1mol / LLiPF6 / EC+DEC+DMC=1:1:1, polypropylene microporous membrane is used as diaphragm, and assembled into button cell. Constant current charge and discharge experiment was carried out in the blue battery test system, the charge and discharge voltage was limited to 0.005V~1.5V, and the battery charge and discharge rate was 0.2C.
[0146] Example First coulombic efficiency (%) Material specific capacity after 100 cycles (mAh / g) Example 1 89.55 957 Example 2 89.58 960 Example 3 89.85 999 Example 4 89.77 981 Example 5 89.68 972 Example 6 89.70 975 Example 7 89.65 969 Example 8 89.63 963 Example 9 89.72 977 Example 10 89.73 979 Embodiment 11 89.45 942 Comparative Example 1 86.82 860 Comparative Example 2 87.56 875 Comparative Example 3 87.78 883 Comparative Example 4 87.02 862 Comparative Example 5 86.53 851 Comparative Example 6 85.97 843 Comparative Example 7 86.66 857 Comparative Example 8 85.52 830 Comparative Example 9 85.30 827
[0147] As can be seen from the above table, the carbon-coated nano-silicon negative electrode materials provided in Examples 1 to 11 have higher first coulombic efficiency and cycle specific capacity than the carbon-coated nano-silicon negative electrode materials provided in Comparative Examples 1 to 9. Specifically, in Comparative Example 1, sodium dodecyl sulfate is selected as the dispersant, which has poor dispersion effect and may even cause the system to be incompatible and agglomerated. Therefore, its effect is significantly worse than that of Example 10, and even worse than that of Example 11 without the addition of a dispersant. In Comparative Example 2, the ball milling time is too long, which will cause the powder to be too fine and destroy the surface structure of the mixed powder, and thus its effect is significantly worse than that of Example 10. In Comparative Example 3, the drying time of step S3 is too short and the water content is large, resulting in the product not being completely dried. In Comparative Examples 4 and 5, the selection of organic carbon sources is different, and the conversion rates of different carbon sources are different. Carbon sources that are not within the scope of this application will result in poor conversion rates and significantly reduced final effects. In Comparative Example 6, the amount of thermite is too large, which will cause too intense combustion, too fast redox reaction, and difficult to control the morphology. In Comparative Example 7, microwave heating is adopted, the microwave power is too large, the redox reaction is too fast, and the morphology is difficult to control. In Comparative Example 8, the mixed powder and thermite are pre-mixed and then ignited. Since thermite is dispersed in the mixed powder, the magnesium bar cannot ignite thermite in time when ignited, resulting in poor redox reaction effect. In Comparative Example 9, the mixed powder is directly ignited. At this time, the mixed powder is difficult to ignite, which makes the redox reaction difficult to proceed, and the final effect is significantly reduced. The above embodiments and comparative examples fully illustrate that the differences in dispersant, organic carbon source, ignition method, premixing method of mixed powder and thermite, as well as too long ball milling time, too much thermite dosage, too short drying time, etc., will lead to a significant reduction in the first coulomb efficiency and cycle specific capacity of the material.
[0148] In summary, the preparation method of the nano silicon-carbon negative electrode precursor provided by the present invention is to mix the organic carbon source and the silicon source to achieve uniform dispersion of the mixed powder, and then use the mixed powder as a reactant, and use the combustion of thermite to provide heat. When the combustion temperature reaches the reaction threshold condition, the organic carbon source and the silicon source undergo a violent redox reaction to generate a carbon shell. At the same time, the energy released by the combustion causes the unreacted silicon source particles to crack and break at high temperature to form nano silicon, thereby obtaining a nano silicon-carbon negative electrode precursor, which simplifies the process. In addition, when the organic carbon source and the silicon source undergo a self-propagating reaction, the generated silicon-carbon material is quickly sprayed into the space, so that the aluminum oxide particles generated by the combustion of thermite rub and collide with the silicon-carbon material. In this process, the aluminum oxide has an interface modification and shaping effect on the outer surface of the coated carbon layer, which improves the unevenness of the outer surface of the carbon layer. After the pole piece is made, the contact area between the outer surface of the carbon layer and other materials is increased, thereby improving the electrical performance of the pole piece.
[0149] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a nano silicon carbon negative electrode precursor, characterized in that: It includes: mixing an organic carbon source and a silicon source to obtain a mixed powder; Ignite the mixed powder with thermite to induce a redox reaction of the mixed powder to obtain a negative electrode precursor; The mass fraction of the thermite in the mixed powder is 1%-5%; the ignition method comprises: inserting a magnesium bar into the thermite, igniting the magnesium bar to ignite the thermite, and initiating a redox reaction in the mixed powder; the redox reaction is carried out in a closed or semi-closed container, the container is provided with a groove for placing the thermite and a plane for spreading the mixed powder, the plane is annularly connected to the side wall of the groove, and the thermite and the mixed powder are in contact with each other at the end of the groove.
2. The method for preparing a nano silicon carbon negative electrode precursor according to claim 1, characterized in that: The thermite comprises aluminum powder and ferric oxide powder in a mass ratio of (0.1-0.5):
1.
3. The method for preparing a nano silicon carbon negative electrode precursor according to claim 1, characterized in that: The magnesium strip was ignited using a pulse igniter.
4. The method for preparing a nano silicon carbon negative electrode precursor according to claim 1, characterized in that: The mass ratio of the organic carbon source to the silicon source in the mixed powder is (0.5-2):1; the organic carbon source is a polymer, and the monomer of the polymer includes at least one of ethylene, propylene, vinyl acetate, vinyl alcohol and ethylene glycol; And / or, the particle size of the organic carbon source is 1 μm to 70 μm; And / or, the silicon source includes at least one of micron silicon, nano silicon and silicon carbide; And / or, the particle size of the silicon source is 200 nm to 3 μm.
5. The method for preparing a nano silicon carbon negative electrode precursor according to claim 4, characterized in that: The particle size of the organic carbon source is 1 μm to 2 μm.
6. The method for preparing a nano silicon carbon negative electrode precursor according to claim 4, characterized in that: The particle size of the silicon source is 600nm-800nm.
7. The method for preparing a nano silicon carbon negative electrode precursor according to claim 4, characterized in that: The polymer includes one or more of a homopolymer or a copolymer composed of the monomers.
8. The method for preparing a nano silicon carbon negative electrode precursor according to claim 7, characterized in that: The copolymer includes at least one of an ethylene-propylene copolymer and an ethylene-vinyl acetate copolymer.
9. The method for preparing a nano silicon carbon negative electrode precursor according to claim 7, characterized in that: The molecular formula of the ethylene-propylene copolymer is (CH2CH2-CH3CHCH2) m or (CH2CH2) a (CH2CHCH2) b , where m ranges from 200 to 1000 and a:b ranges from (4 to 10):
1.
10. The method for preparing a nano silicon carbon negative electrode precursor according to claim 7, characterized in that: The molecular formula of the ethylene-vinyl acetate copolymer is (CH2CH2-CH2CHCOOCH3) m or (CH2CH2) a (CH2CHCOOCH3) b , where m ranges from 300 to 800, and a:b ranges from (2 to 6):
1.
11. The method for preparing a nano silicon carbon negative electrode precursor according to any one of claims 1 to 10, characterized in that: When the organic carbon source and the silicon source are mixed, a dispersant is also added.
12. The method for preparing a nano silicon carbon negative electrode precursor according to claim 11, characterized in that: The total mass fraction of the organic carbon source and the silicon source in the mixed powder is 97% to 99.5%, and the mass fraction of the dispersant is 0.5% to 3%.
13. The method for preparing a nano silicon carbon negative electrode precursor according to claim 11, characterized in that: The dispersant includes at least one of PE wax powder, polyacrylate, sulfonate and hydroxyethyl cellulose.
14. The method for preparing a nano silicon carbon negative electrode precursor according to any one of claims 1 to 10, characterized in that: The mixing includes at least one of stirring, ball milling and grinding.
15. The method for preparing a nano silicon carbon negative electrode precursor according to claim 14, characterized in that: The ball mill has a rotation speed of 300 to 800 rpm and a ball milling time of 1 to 10 hours.
16. A nano silicon-carbon negative electrode material, characterized in that: The nano silicon-carbon negative electrode precursor is prepared by post-processing the nano silicon-carbon negative electrode precursor prepared by the method for preparing the nano silicon-carbon negative electrode precursor according to any one of claims 1 to 15.
17. The nano silicon-carbon negative electrode material according to claim 16, characterized in that: The post-treatment includes pickling, washing and drying the nano silicon carbon negative electrode precursor.
18. The nano silicon-carbon negative electrode material according to claim 17, characterized in that: The pickling includes washing with a pickling solution having a concentration of 0.5 to 1.5 mol / L.
19. The nano silicon carbon negative electrode material according to claim 18, characterized in that: The pickling solution includes at least one of hydrochloric acid, sulfuric acid or nitric acid.
20. The nano silicon-carbon negative electrode material according to claim 17, characterized in that: The washing comprises washing with an ethanol-water solution, wherein the mass ratio of ethanol to water in the ethanol-water solution is (0.5-2):
1.
21. The nano silicon-carbon negative electrode material according to claim 17, characterized in that: The drying temperature is 50-80° C. and the drying time is 3-6 hours.
22. The nano silicon-carbon negative electrode material according to any one of claims 16 to 21, characterized in that: The particle size of the nano silicon carbon negative electrode material is 20nm-1μm.
23. The nano silicon-carbon negative electrode material according to any one of claims 16 to 21, characterized in that: The particle size of the nano silicon carbon negative electrode material is 100nm to 700nm.
24. The nano silicon-carbon negative electrode material according to any one of claims 16 to 21, characterized in that: The particle size of the nano silicon carbon negative electrode material is 200nm to 500nm.
Citation Information
Patent Citations
Preparation method of coated carbon-silicon negative electrode material
CN111960421A
Chemical furnace synthesis method of SiB6
CN114409412A
Cited By
Silicon-carbon negative electrode material coated with amorphous metal compound doped carbon composite layer and preparation method of silicon-carbon negative electrode material
CN121748326A